1972
DOI: 10.1515/zna-1972-0107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Cresyl Violet Laser

Abstract: The properties of flashlamp-and laser-pumped cresyl violet lasers emitting between 620 and 710 nm were studied. In mixed cresyl violet-rhodamine 6G solutions, the excitation efficiency was found to be enhanced by more than a factor of two, the major part of the excitation energy being supplied by the rhodamine 6G fluorescence radiation.Self-modelocking in a 3-component solution, containing cresyl violet, rhodamine 6G and a saturable absorber dye, was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…For example, Rhodamine 6G-Cresyl violet mixtures are reported [4,5] to have enhanced the laser efficiency of Cresyl violet, and RhodamineB-DODC mixture has enabled the generation of tunable near infrared radiation with nitrogen laser pumping [6]. This type of excitation transfer is called "sensitized fluorescence" and is well known in photochemistry [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rhodamine 6G-Cresyl violet mixtures are reported [4,5] to have enhanced the laser efficiency of Cresyl violet, and RhodamineB-DODC mixture has enabled the generation of tunable near infrared radiation with nitrogen laser pumping [6]. This type of excitation transfer is called "sensitized fluorescence" and is well known in photochemistry [7].…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of electronic excitation energy from a donor to an acceptor molecule generally takes place either by a direct coupling (collisional transfer or resonance transfer of the excitation due to long-range dipole-dipole interaction, i.e., non-radiative energy transfer referred to as FRET) or by a fluorescence-absorption process (radiative transfer), if the two spectra, i.e., the fluorescence of the donor and the absorption of the acceptor, are sufficiently overlapped [19][20][21]. Energy transfer between D & A dye molecules is an important mechanism used for various purposes, for example, extending the lasing wavelength [22], enhancement in tunability [23], and also increasing the power of dye lasers [24][25][26][27]. Many reports on energy transfer in organic dyes are available with a number of donoracceptor (D-A) pairs using Rhodamine-6G [28][29][30][31][32][33][34] or Rhodamine-B as an acceptor [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Rhodamine 6G (Rh6G) -cresyl violet (CV) is one of the popular energy transfer systems [22,23]. The addition of Rh6G was reported to enhance the lasing efficiency of CV [24]. Using this system, Basheer et al have reported the pump-power dependence and effect of the acceptor concentration in a prism-type geometry [14,25,26].…”
Section: Introductionmentioning
confidence: 99%